Correlations between intimate partner violence and spontaneous abortion, stillbirth, and neonatal death in rural Malawi1. Issue 1 (15th May 2017) - Rao, Nisha; Norris Turner, Abigail; Harrington, Bryna; Nampandeni, Patrick; Banda, Venson; Norris, Alison
Abstract: Objective: To characterize associations between intimate partner violence (IPV) and adverse delivery outcomes among married Malawian women. Methods: In the present secondary analysis of an ongoing project investigating sexual and reproductive health decision making in rural, Lilongwe District, Malawi, married women who had experienced at least one pregnancy were interviewed between July 15, 2014, and February 25, 2015. Associations between physical IPV experienced with participants' current partners and history of adverse delivery outcomes (spontaneous abortions, stillbirths, and neonatal deaths) were examined using log‐binomial regression. Results: The analyses included 792 women. The 166 (21.0%) participants who reported having experienced physical IPV with their current partner were significantly more likely to have a history of adverse delivery outcomes in the unadjusted (prevalence ratio 1.23; 95% confidence interval 1.08–1.41) and adjusted (adjusted prevalence ration 1.19; 95% CI 1.01–1.40) analyses. Conclusion: Physical IPV was reported by a large proportion of participants in the present study and was significantly associated with adverse delivery outcomes. Public health interventions providing physical IPV screening and referral to support services could help improve maternal and child health in Malawi. Abstract : Physical IPV was significantly associated with adverse delivery outcomes—a composite outcome of spontaneous abortions, stillbirths, and neonatal deaths—among women in rural Malawi.